Chloroplast microsatellite markers for Artocarpus (Moraceae) developed from transcriptome sequences1. (10th September 2015) - Gardner, Elliot M.; Laricchia, Kristen M.; Murphy, Matthew; Ragone, Diane; Scheffler, Brian E.; Simpson, Sheron; Williams, Evelyn W.; Zerega, Nyree J. C.
Abstract : Premise of the study: Chloroplast microsatellite loci were characterized from transcriptomes of Artocarpus altilis (breadfruit) and A. camansi (breadnut). They were tested in A. odoratissimus (terap) and A. altilis and evaluated in silico for two congeners. Methods and Results: Fifteen simple sequence repeats (SSRs) were identified in chloroplast sequences from four Artocarpus transcriptome assemblies. The markers were evaluated using capillary electrophoresis in A. odoratissimus (105 accessions) and A. altilis (73). They were also evaluated in silico in A. altilis (10), A. camansi (6), and A. altilis × A. mariannensis (7) transcriptomes. All loci were polymorphic in at least one species, with all 15 polymorphic in A. camansi . Per species, average alleles per locus ranged between 2.2 and 2.5. Three loci had evidence of fragment‐length homoplasy. Conclusions: These markers will complement existing nuclear markers by enabling confident identification of maternal and clone lines, which are often important in vegetatively propagated crops such as breadfruit.